2006
DOI: 10.1002/mus.20520
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological subtypes and prognosis of childhood Guillain–Barré syndrome in Japan

Abstract: Guillain-Barré syndrome (GBS) is classified into acute inflammatory demyelinating polyneuropathy (AIDP) and acute motor axonal neuropathy (AMAN), but little is known about the incidence of the subtypes and the prognosis of childhood GBS. To elucidate the features and long-term prognosis, clinical and electrophysiological data for 31 Japanese GBS children were reviewed. By electrodiagnostic criteria, children were classified as having AIDP (35%) or AMAN (48%), or were unclassified (16%). The AMAN children invar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
(45 reference statements)
7
47
2
3
Order By: Relevance
“…[23] In contrast, a number of reports showed that in North America, most GBS children appear to have AIDP, although these reports did not employ the same electrodiagnostic criteria for AIDP or AMAN as used in this study. [22] These findings suggest that the incidence of AMAN in childhood GBS varies considerably among countries, as it does in the adult population. The reason is unknown, but preceding infectious agents and host factors may be responsible, as postulated for adult GBS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[23] In contrast, a number of reports showed that in North America, most GBS children appear to have AIDP, although these reports did not employ the same electrodiagnostic criteria for AIDP or AMAN as used in this study. [22] These findings suggest that the incidence of AMAN in childhood GBS varies considerably among countries, as it does in the adult population. The reason is unknown, but preceding infectious agents and host factors may be responsible, as postulated for adult GBS.…”
Section: Discussionmentioning
confidence: 94%
“…[21] In a Japanese study, the proportion of children with AIDP (35%) was similar to that of children with AMAN (48%), and recovery was generally favorable in both subtypes. [22] When pediatric GBS patients were classified according to axonal or myelin involvement, their functional status 12 months after onset did not differ and was good in both, and a similar study showed that the duration of ventilatory support did not differ significantly. [2324] We found that 69.4% of the patients was AIDP type, 27.8% AMAN type and 2.8% AMSAN type.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of Japanese children with GBS, a slightly greater incidence of AMAN was reported. 24 GBS subtypes tend to occur in different age groups. In Europe and North America, where AIDP is the leading GBS subtype, the GBS incidence increases steadily with advancing age.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is important to follow-up patients regularly (9). Nagasawa et al (9) reported in their study that 80% of patients with AMAN could walk within six months from the beginning of the symptoms, but this period might sometimes be two years. Moreover, Hiraga et al (3) stated that AMAN patients with a severe clinical picture could not regain their ability to walk in the first six months, and a complete healing could last a longer time.…”
Section: Discussionmentioning
confidence: 96%